Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)